Tax Compliance Analysis : Collection and Equalization of Income Tax Article 21 and Value Added Tax - Muhamad Rifki Fadillah; M. Hendri Yan Nyale (Enrichment : Journal of Management, 2022)
The purpose of this study is to examine whether the collection of SPT PPN and SPT PPh 21 in the company is in accordance with tax regulations and also to review the tax equalization technique tools to minimize the issuance of letters requesting explanations and information (SP2DK) and Tax Bills (STP) from the tax office. . The results of the study found that the collection of SPT PPN and SPT PPh21 was in accordance with applicable tax regulations. For VAT deposits because the collection is made to the treasurer and the VAT is deposited by the government treasurer in accordance with PMK 231/PMK.03/2019. The collection and withholding of PPh21 carried out by PT.ABC was in accordance with the PPh Law Number 36 of 2008. It was found that there were still delays in reporting VAT payments and reports during the period of February 2019, September-November 2020 and July-August 2021. Deposits and reporting of PPh21 PT.ABC found that there were still delays in depositing in January-June 2019, January-March 2020 and February 2020 and late reporting in January-May 2019, December 2020 and no delays in 2021. From the results of the equalization there was a difference in income in in the VAT SPT with income in the 2019-2021 corporate annual income tax return due to lack of supervision from the company and system errors from e-invoicing. However, there is no difference between the cost of salaries in the SPT PPh21 and the cost of salaries in the corporate income tax return for the 2019-2021 period.